In vitro and in vivo antitumoral activity of a ternary copper (II) complex - Lopes, Jeyson Césary; Botelho, Françoise Vasconcelos; Barbosa Silva, Marcelo José; Silva, Suélen Fernandes [UNESP]; Polloni, Lorena; Alves Machado, Pedro Henrique; Rodrigues de Souza, Tiago; Goulart, Luiz Ricardo; Silva Caldeira, Priscila Pereira; Pereira Maia, Elene Cristina; Morelli, Sandra; de Oliveira-Júnior, Robson J. (My University, 2020)
Recently, a high number of copper derivatives has been evaluated as DNA-targeting metallodrugs, due to the lower toxicity and its potential to cleave DNA. Several strategies have been testing to develop metal compounds effective against tumour cells. In this work, the ternary copper (doxycycline)-(1,10-phenanthroline) complex [Cu(dox)(phen)]2+ was especially designed as an antitumoral drug, previously showing high cytotoxicity and DNA cleavage activity. We aimed to further investigate the in vitro cytotoxic activity in both tumoral and non-tumoral cells, in vitro genotoxic potential, and in vivo antitumor activity using BALB/C mouse injected with sarcoma S180 and Ehrlich cell lines. Our results indicated that this compound exhibits a moderate genotoxic potential, with selective growth inhibition of tumor cells, especially the murine melanoma B16F10. Its main mechanism of action seems to be through ROS generation. We have further shown a significant reduction of the implanted tumor size in the animal model, suggesting that this compound has great antitumoral potential against many tumor types. [Cu(dox)(phen)]2+ is selectively cytotoxic for melanoma B16F10 and showed high chemotherapeutic potential in vivo against implanted sarcoma S180 and Ehrlich ascites tumours.
Keywords: Antitumoral activity; Cytotoxicity; Genotoxicity; Melanoma; Sarcoma; Ternary copper (II) complex